Chemokine receptor CCR6‐dependent accumulation of γδ T cells in injured liver restricts hepatic inflammation and fibrosis. Issue 2 (23rd December 2013) - Hammerich, Linda; Bangen, Jörg M.; Govaere, Olivier; Zimmermann, Henning W.; Gassler, Nikolaus; Huss, Sebastian; Liedtke, Christian; Prinz, Immo; Lira, Sergio A.; Luedde, Tom; Roskams, Tania; Trautwein, Christian; et al.
<x xml:space="preserve">Abstract</x> Chronic liver injury promotes hepatic inflammation, representing a prerequisite for organ fibrosis. We hypothesized a contribution of chemokine receptor CCR6 and its ligand, CCL20, which may regulate migration of T‐helper (Th)17, regulatory, and gamma‐delta (γδ) T cells. CCR6 and CCL20 expression was intrahepatically up‐regulated in patients with chronic liver diseases (n = 50), compared to control liver (n = 5). Immunohistochemistry revealed the periportal accumulation of CCR6+ mononuclear cells and CCL20 induction by hepatic parenchymal cells in liver disease patients. Similarly, in murine livers, CCR6 was expressed by macrophages, CD4 and γδ T‐cells, and up‐regulated in fibrosis, whereas primary hepatocytes induced CCL20 upon experimental injury. In two murine models of chronic liver injury (CCl4 and methionine‐choline‐deficient diet), Ccr6−/− mice developed more severe fibrosis with strongly enhanced hepatic immune cell infiltration, compared to wild‐type (WT) mice. Although CCR6 did not affect hepatic Th‐cell subtype composition, CCR6 was explicitly required by the subset of interleukin (IL)‐17‐ and IL‐22‐expressing γδ T cells for accumulation in injured liver. The adoptive transfer of WT γδ, but not CD4 T cells, into Ccr6−/− mice reduced hepatic inflammation and fibrosis in chronic injury to WT level. The anti‐inflammatory function of hepatic γδ T cells was independent of IL‐17, as evidenced by transfer of Il‐17−/− cells. Instead, hepatic γδ T cells colocalized with hepatic stellate cells (HSCs) in vivo and promoted apoptosis of primary murine HSCs in a cell‐cell contact‐dependent manner, involving Fas‐ligand (CD95L). Consistent with γδ T‐cell‐induced HSC apoptosis, activated myofibroblasts were more frequent in fibrotic livers of Ccr6−/− than in WT mice. Conclusion: γδ T cells are recruited to the liver by CCR6 upon chronic injury and protect the liver from excessive inflammation and fibrosis by inhibiting HSCs. (Hepatology 2014;59:630–642)